Efektivitas Penggunaan Media Digital dalam Pembelajaran Bahasa Indonesia bagi Penutur Asing - Junhari Ariandi (Journal of Language Studies, 2025)
The rapid advancement of digital technology has transformed the landscape of language education, including the teaching of Indonesian as a Foreign Language (BIPA). This study explores the effectiveness of digital media in facilitating the acquisition of the Indonesian language by foreign learners. The purpose of this research is to investigate how digital platforms—such as learning management systems, mobile applications, video conferencing tools, and interactive content—enhance the linguistic and communicative competence of BIPA students. A descriptive qualitative method was employed, using literature review as the main approach to synthesize findings from previous studies. Data were collected from scholarly articles, academic books, and reports relevant to the topic. The findings indicate that the use of digital media significantly improves student engagement, motivation, and understanding of linguistic structures and sociocultural contexts. Moreover, digital tools allow for more personalized learning experiences and real-time interaction with native speakers. However, the study also identifies challenges such as digital literacy gaps, infrastructure limitations, and the risk of cultural disconnection. In conclusion, digital media, when effectively integrated, can serve as a powerful means to enhance BIPA instruction, provided it is supported by pedagogical strategies and adequate teacher training.